2001
DOI: 10.1046/j.1526-0992.2001.007001015.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Ecosystem Health Indicators in Centro Habana: A Community‐based Approach

Abstract: A set of interventions was undertaken between 1995 and 1999 to improve the quality of life and human health in Cayo Hueso, an inner city community in Central Havana. The municipality and community organizations contacted the agency responsible for public and environmental health in Cuba (INHEM) to evaluate whether these improvements were as effective and efficient as possible, so as to assist in planning further interventions in this and other communities. With the aid of international researchers, an effort w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The ecosystem health literature (e.g., Schaeffer et al 1988, Costanza et al 1992 proposes measurement in terms of vigor, organization, and resilience (Costanza 2012), and is generally associated with a utilitarian value and western understandings of ecosystems. The term ecosystem health can be used without reference to feedbacks with people, though some authors do recognize these links (Tiwari et al 1998, Spiegel et al 2001, Tzoulas et al 2007). We believe that using the same term "wellbeing" for humans as well as nonhumans helps reinforce interactions and processes between humans and nature.…”
Section: Nature Should Be Given a Voicementioning
confidence: 99%
“…The ecosystem health literature (e.g., Schaeffer et al 1988, Costanza et al 1992 proposes measurement in terms of vigor, organization, and resilience (Costanza 2012), and is generally associated with a utilitarian value and western understandings of ecosystems. The term ecosystem health can be used without reference to feedbacks with people, though some authors do recognize these links (Tiwari et al 1998, Spiegel et al 2001, Tzoulas et al 2007). We believe that using the same term "wellbeing" for humans as well as nonhumans helps reinforce interactions and processes between humans and nature.…”
Section: Nature Should Be Given a Voicementioning
confidence: 99%
“…The integrating DPSEEA framework (driving forcepressure-state-exposure-effect/action) (Briggs, 1999), elaborated by the World Health Organization (Corvalan et al, 1996), was presented in workshops and was rapidly embraced to define indicators at the individual, household, and neighborhood level (Spiegel et al, 2001a) For example, as shown in Table 1, it was noted that weak economic growth constituted a key driving force influencing the need of intervention, through a creative blend of targeting scarce resources and mobilizing community capacities. At the level of pressures, for example, the cost of repairs and proportion of families willing to undertake these were considered indicators relevant for the housing intervention; the proportion of people unemployed was listed as a relevant indicator of pressure in the sociocultural domain, along with the funds allocated for such initiatives.…”
Section: Methods For Evaluating the Effectiveness Of The Plan Cayo Huesomentioning
confidence: 99%
“…This mass mobilization of local and national resources allowed the following interventions to be carried out (Spiegel et al, 2001a):…”
Section: Plan Cayo Hueso (The Intervention)mentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in the review of urban ecosystem health assessment (Su et al, 2010), different frameworks, including performance of healthy cities (Takano and Nakamura, 1998), subsystem model (Guo et al, 2002), driving force-pressure-state-exposure-effectaction model (Spiegel et al, 2001), have been used to establish health indicators of the urban ecosystem from aspects of social, economic, ecological, and human health. The attempt to measure changes in human and societal health and well-being along with those related to the integrity of natural ecosystems (McMullan, 1997) are regarded as the common characteristics amongst these different models and indicators of urban ecosystem health.…”
Section: Introductionmentioning
confidence: 99%